A longitudinal criterion-related validation and norming of a scholastic aptitude test implications for admissions policy and decision making - Domingo, Apolonio Salvador 1931- (1985)
This study validated, established norms and item analyzed the College Freshman Admission Test (CFAT) of the Mariano Marcos State University, using the SPSS Multiple Regression Analysis for longitudinal validation; Pearson r for test stability reliability; Point Biserial r for prediction of graduation; Kuder-Richardson Formula 21 for internal consistency and Top and Bottom 27 percent for item analysis. The CFAT composite score predicts Grade Point Average (GPA) in all year levels of degree programs in agriculture, nursing, and secondary and elementary education. Subtests in comprehension, verbal facility, composition, science and mathematics significantly predict Freshman GPA. Intellective and non-intellective variables jointly interact in predicting scholastic performance with comprehension, verbal facility, degree programs, secondary curriculum and abstract reasoning jointly accounting for 61 percent of Freshman GPA variance. Comprehension, secondary curriculum, degree program and verbal facility together affect longitudinal validity.
Mimeographed.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Vita.
Keywords: Universities and colleges -- Entrance examinations; College entrance achievement tests